2014
DOI: 10.1016/j.jpedsurg.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections in infants admitted to the neonatal intensive care unit

Abstract: Background-Surgical interventions are common in infants admitted to the neonatal intensive care unit (NICU). Despite our awareness of the broad impact of surgical site infection (SSI), there is little data in neonates. Our objective was to determine the rate and clinical impact of SSI in infants admitted to the NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 28 publications
4
44
0
1
Order By: Relevance
“…We report no infectious complications or sepsis in our patients perhaps due to shortened ventilation time as well as avoidance of early surgical closure which has been linked with higher risk of infection. [23] Our data indicate that delayed surgical closure of these infants is not associated with greater complications or longer neonatal stay time. Our mean day to closure was 331 days relative to 92 days in past report (including primary closure) [4].…”
Section: Accepted Manuscriptmentioning
confidence: 52%
See 1 more Smart Citation
“…We report no infectious complications or sepsis in our patients perhaps due to shortened ventilation time as well as avoidance of early surgical closure which has been linked with higher risk of infection. [23] Our data indicate that delayed surgical closure of these infants is not associated with greater complications or longer neonatal stay time. Our mean day to closure was 331 days relative to 92 days in past report (including primary closure) [4].…”
Section: Accepted Manuscriptmentioning
confidence: 52%
“…If the omphalocele was ruptured (one case),the sac was repaired with running suture before application of the first dressing [14]. In this case, the sac ruptured during delivery and was repaired by a running a 4-0 vicryl suture.…”
Section: Giant Omphalocele Managementmentioning
confidence: 99%
“…Both of which hare associated with complications. A review of 143 patients found a 60% secondary sepsis rate due to prolonged (median 34.8 days) mechanical ventilation in infants born with gastroschisis and omphaloceles [17]. Our first infant was intubated for only 31 days and had no perinatal complications.…”
Section: Discussionmentioning
confidence: 79%
“…A study of 724 patients found a strong correlation between early surgical closure (within 85 days) and surgical site infections (p < 0.0001) [17]. We, and others, have previously reported lower rates of surgical site infection with delayed surgical closure [4,19,20].…”
Section: Discussionmentioning
confidence: 82%
“…Higher rates of surgical site infection defined as superficial, deep, and organ infections within 30 days of surgical procedures were noted among infants following closure of gastroschisis. 45 It is important to closely monitor infants with surgical site infection because they require significantly longer hospital stay. 45…”
Section: Surgical Treatment Optionsmentioning
confidence: 99%